EFFICACY OF ONLINE VENDOR PLATFORMS IN ENHANCING MICRO-BUSINESS PERFORMANCE OF STUDENTS IN UNIVERSITIES (NAU Journal of Technology and Vocational Education, 2026)
The study examined efficacy of online vendor platforms in enhancing micro-business performance of students in universities. Descriptive survey research design was used in the study. Two research questions guided the study, and two hypotheses were tested at 0.05 level of significance. Population of study comprised 150 students in 2024/2025 academic session at Alex Ekwueme Federal University Ndufu Alike Ikwo (AE-FUNAI) who engage in micro-businesses using online platforms. A structured questionnaire that was validated by two experts from Technology Education and one of the experts, from Measurement and Evaluation unit, AE_FUNAI was used. Trial testing method was used to determine reliability, which yielded 0.89, and 0.75, as being reliable. Data collection was done using online data collection approach (Google form) and analyzed using mean and standard deviation for research questions, and hypotheses testing using t-test analysis. The result revealed that online vendor platforms have positive efficacy in enhancing students’ micro-business performance as it encourages students to acquire more customers and make profits. Hence, researchers recommend among others that; educational institutions should provide training programmes focused on digital marketing, e-commerce strategies, and data analytics for student entrepreneurs to enhance performance of micro -businesses in universities.
Keywords: Online Vendor; Online Platforms; Micro-Businesses; Micro-Business Performance